The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/pr200864j
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Polysaccharide-Degrading Proteome of Butyrivibrio proteoclasticus

Abstract: Plant polysaccharide-degrading rumen microbes are fundamental to the health and productivity of ruminant animals. Butyrivibrio proteoclasticus B316(T) is a gram-positive, butyrate-producing anaerobic bacterium with a key role in hemicellulose degradation in the rumen. Gel-based proteomics was used to examine the growth-phase-dependent abundance patterns of secreted proteins recovered from cells grown in vitro with xylan or xylose provided as the sole supplementary carbon source. Five polysaccharidases and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 56 publications
(86 reference statements)
2
33
0
Order By: Relevance
“…Therefore, even if the different methods and different ruminant breeds were used, Butyrivibrio dominated the stomach of ruminants. Dunne et al demonstrated that Butyrivibrio could modulate the secretion of hemicelluloses-degrading enzymes [22], which supported the notion that this organism made an important contribution to polysaccharide degradation in the rumen. In addition, Butyrivibrio is an important butyrate producer, and promotes the stomach epithelium proliferation.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, even if the different methods and different ruminant breeds were used, Butyrivibrio dominated the stomach of ruminants. Dunne et al demonstrated that Butyrivibrio could modulate the secretion of hemicelluloses-degrading enzymes [22], which supported the notion that this organism made an important contribution to polysaccharide degradation in the rumen. In addition, Butyrivibrio is an important butyrate producer, and promotes the stomach epithelium proliferation.…”
Section: Discussionmentioning
confidence: 91%
“…The software TMHMM 2.0 and PSORT Version 3.0 were separately used to predict transmembrane domains and cellular localizations. Protein functions were assigned using Tigrfam and BLASTp [74]. …”
Section: Methodsmentioning
confidence: 99%
“…Kelly et al [9] proposed a mechanism of extracellular polysaccharide breakdown whereby a group of nine cell-associated proteins that target xylan, pectin, and starch form the core of the extracellular catalytic potential. Recent examination by two-dimensional electrophoresis (2DE) of the extracellular polysaccharide-degrading proteome of B. proteoclasticus supported this mechanism [10], and demonstrated that at least four (Xyn10B, Xsa43J, Pme8B, and Pel1A) of the nine extracellular enzymes are secreted when cells are grown using xylan as the only hemicellulosic carbon source. The endo-1,4-β-xylanase Xyn10B was significantly more abundant in the culture medium of xylan-grown cells, which suggests it plays a primary role in B. proteoclasticus mediated hemicellulose degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the secreted xylosidase/arabinofuranosidase Xsa43J is expected to hydrolyze xylobiose, arabinoxylans and arabinogalactans. Several ATP-binding cassette (ABC) transporter substrate-binding proteins were also found to be significantly more abundant in the xylan-grown cell culture medium [10], and in the membrane proteome [13], which implies they are important for uptake of oligosaccharides derived from xylan disassembly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation